تعليم المفردات باستخدام وسائل الصور المتحركة (دراسة تجريبية في المدرسة الثانوية الإسلامية الحكومية 11 فيدي) - Miswarul Abdi Aziz (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
The purpose of this study is to determine students’ responses in vocabulary learning after using moving picture media at MTsN 11 Pidie, as well as to determine the effectiveness of using moving picture media in vocabulary learning at MTsN 11 Pidie. The research method used by researchers in completing this study is an experimental research method with a one-group pre-test and post-test design. The data collection techniques used by researchers are observation, questionnaire, test, and documentation. The results showed that students’ responses in vocabulary learning after using moving picture media at MTsN 11 Pidie showed high interest. The moving picture media encourages students to memorize vocabulary, and the use of moving picture media is proven to be effective and influential in improving students’ ability to memorize vocabulary at MTsN 11 Pidie. This is based on the t-test results, where the t-count value is smaller than the negative t-table value or (-17,610 < -1,740).